A novel supramolecular AIE π-gel for fluorescence detection and separation of metal ions from aqueous solution. Issue 32 (26th July 2019) - Wei, Tai-Bao; Zhang, Qin-Peng; Fan, Yan-Qing; Mao, Peng-Peng; Wang, Jiao; Guan, Xiao-Wen; Zhang, You-Ming; Yao, Hong; Lin, Qi
Abstract : A novel supramolecular AIE π-gel (ONT ) is constructed using a π–π stacking interaction and hydrogen bonding interaction, which could efficiently detect and separate metal ions. Abstract : A novel supramolecular aggregation induced emission (AIE) π-gel (ONT ) was constructed by using a functionalized trimesic amide (TCP ) molecule assembled with a bis-pyridine functionalized naphthalene diimide (ND ) molecule using a non-covalent interaction. TheONT showed strong AIE at 468 nm. Furthermore, theONT could detect and adsorb ferric (Fe 3+ ) or cupric (Cu 2+ ) ions from water. Meanwhile, a thin film based on supramolecular AIE π-gelONT was prepared, which could be used as a fluorescent security display material for detecting Fe 3+ or Cu 2+ . Thus, the AIE π-gelONT shows potential for practical applications in efficient multi-analyte detection and separation and as a fluorescent display material.